Hydrogen-rich syngas produced from the co-pyrolysis of municipal solid waste and wheat straw - Jun, Zhao; Shuzhong, Wang; Zhiqiang, Wu; Haiyu, Meng; Lin, Chen (International journal of hydrogen energy, 2017)
The co-thermochemical conversion of Municipal Solid Waste (MSW) and biomass is a new environmental technology and can produce hydrogen-rich syngas. This study investigated the co-pyrolysis of MSW and wheat straw, using a drop-tube furnace experiment. Using a temperature range of 500 °C–1000 °C, the study assessed pyrolysis gas yield, product distribution, gas low heating value, and carbon conversion of co-pyrolysis MSW with different amounts of wheat straw. Adding wheat straw only slightly increases the gas yield and carbon conversion, but improved the carbon monoxide and carbon dioxide in the syngas. At an experimental temperature below 700 °C, adding wheat straw promoted the cracking reaction of hydrocarbon gas, generated by the pyrolysis of MSW. At a temperature of 600 °C, adding 25% wheat straw improved carbon conversion in the blended sample. This study provides a basis for the application of MSW and WS thermo-chemical conversion. •Obtain production distribution of fast pyrolysis MSW and WS from 500 °C to 1000 °C.•Obtain Syngas yields, LHV and carbon conversion of co-pyrolysis MSW and WS.•At 600 °C, adding 25% WS to MSW achieve the maximum gas phase carbon conversion.